ASSESSING UNEMPLOYMENT RATES IN TANAH DATAR REGENCY: INSIGHTS FROM SMALL AREA ESTIMATION - Winanda, Rara Sandhy; Khairani, Yasyfin Ikrima; Permana, Fajar Wisga (BAREKENG: Jurnal Ilmu Matematika dan Terapan, 2025)
Unemployment is a significant issue in Indonesia's labor market. The unemployment rate is measured by the Open Unemployment Rate (OUR) through the National Labor Force Survey (SAKERNAS) conducted by BPS. In 2022, the OUR in Tanah Datar District reached its highest level in the past fifteen years. This rise in unemployment contrasts with the declining poverty rate, unlike other districts/cities in West Sumatra. To address the increasing unemployment, detailed information at the smallest administrative level is necessary. However, because the limited sample size in SAKERNAS does not allow for direct estimation of the OUR with sufficient accuracy, this study aims to overcome this limitation by estimating the OUR at the subdistrict level using indirect estimation through Small Area Estimation (SAE). The SAE method applied is Empirical Best Linear Unbiased Prediction (EBLUP), using the Restricted Maximum Likelihood (REML) estimation model. This research uses secondary data obtained from the National Labor Force Survey (SAKERNAS) of Tanah Datar Regency for the August 2022 period and the Village Potential data (PODES) of Tanah Datar Regency in 2021. The findings indicate that three subdistricts—Pariangan, Lintau Buo Utara, and Padang Ganting—have higher OUR values than Tanah Datar Regency in 2022, with rates of 6.00%, 6.01%, and 11.03%, respectively. The factor that influences the high OUR in these sub-districts is the variable percentage of the male population, which in this model has a large contribution to the calculation of OUR. The indirect estimations using EBLUP are deemed reliable, as the RSE value is below 25%. Therefore, the EBLUP indirect estimation results for OUR at the subdistrict level in Tanah Datar Regency can guide local government efforts to take targeted actions to reduce unemployment, especially in areas with high OUR.